2021
DOI: 10.2147/bctt.s176514
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Pertuzumab and Trastuzumab in the Treatment of HER2-Positive Early Breast Cancer: A Review of the Emerging Clinical Data

Abstract: Human epidermal growth factor receptor type 2 (HER2) is a relevant and effective target in breast cancer. The development of monoclonal antibodies against HER2 has revolutionized the treatment of HER2-positive breast cancer. The humanized monoclonal antibody, trastuzumab, was the first in its class to be widely adopted. It was initially studied in the metastatic setting and then in the treatment of early-stage disease, demonstrating significant improvement in overall survival in both settings. The addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 70 publications
(95 reference statements)
0
18
0
Order By: Relevance
“…Other authors have reported similar outcomes in larger patient series and concluded that neoadjuvant chemotherapy with TZ + PZ increases the pCR rate compared with trastuzumab alone to one of around 50-70% [6]. However, it should be mentioned that approximately one-third of patients with HER2-positive early BC treated with TZ experience relapse [16]. This highlights a need to find good biomarkers of the efficacy of anti-HER2 treatment for this aggressive BC phenotype.…”
Section: Discussionmentioning
confidence: 88%
“…Other authors have reported similar outcomes in larger patient series and concluded that neoadjuvant chemotherapy with TZ + PZ increases the pCR rate compared with trastuzumab alone to one of around 50-70% [6]. However, it should be mentioned that approximately one-third of patients with HER2-positive early BC treated with TZ experience relapse [16]. This highlights a need to find good biomarkers of the efficacy of anti-HER2 treatment for this aggressive BC phenotype.…”
Section: Discussionmentioning
confidence: 88%
“…In this sense, the rationale for a combination of trastuzumab with either chemotherapy such as capecitabine or paclitaxel, or with tyrosine kinase inhibitors such as lapatinib, or more recently with a dual inhibitor of both mTOR and PI3K, has proved to be a more potent approach for HER-2-positive breast cancer treatment than trastuzumab alone [ 24 ]. Nowadays, the combined therapy of trastuzumab, pertuzumab, and taxane is the standard for treating metastatic breast cancer [ 25 ]. Our results indicated that PPRHs could be a potential tool in combination therapies with trastuzumab since their gene silencing mechanism contributed to increasing the effect on cell viability with respect to the antibody alone.…”
Section: Discussionmentioning
confidence: 99%
“…The current treatment of choice for Her2 + breast cancer encompasses the use of the humanized anti-Her2 mAbs trastuzumab and pertuzumab [ 36 ], which have recently been demonstrated to be more effective when co-administered [ 10 ]. Experimentally, the cooperative and synergic effects of mAb combination, in terms of antitumor potential, can be achieved through DNA vaccination [ 19 , 20 , 25 ], which also has the advantage of inducing an active and long-lasting immunological memory able to prolong the therapeutic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These mAbs can be used to deliver drugs to the tumor, as in the case of trastuzumab emtansine and trastuzumab deruxtecan [ 5 ], but their main application is to interfere with Her2 signaling and induce tumor cell killing by immune cells or the complement system [ 6 , 7 , 8 , 9 ]. Emerging clinical data support their combined administration to avoid resistance and increase efficacy [ 10 ]. While the ability to induce antibody-dependent cellular cytotoxicity (ADCC) is a proven essential mechanism of their efficacy [ 6 , 7 ], more controversial is the role of complement-mediated cytotoxicity (CDC) and complement-mediated cellular cytotoxicity (CDCC) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%